2022
DOI: 10.1177/19476035221142010
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Use of FGF-18 Augmentation for Improving Cartilage Healing Following Surgical Repair: A Systematic Review

Abstract: Objective To evaluate the efficacy of fibroblast growth factor-18 (FGF-18) augmentation for improving articular cartilage healing following surgical repair in preclinical ( in vivo) animal models. Design A systematic review was performed evaluating the efficacy of FGF-18 augmentation with cartilage surgery compared with cartilage surgery without FGF-18 augmentation in living animal models. Eligible intervention groups were FGF-18 treatment in conjunction with orthopedic procedures, including microfracture, ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…FGF-18, which is highly expressed in the superficial zone of AC, stimulates the expression and accumulation of COL2 and proteoglycan in articular chondrocytes [ 148 , 149 ], preserving cartilage phenotype and thickness to protect AC against degeneration [ 112 ]. DePhillipo et al [ 150 ] confirmed significant improvement in cartilage healing at 6 months after microfracture or osteochondral defect repair in preclinical randomized controlled trials with the use of FGF-18.…”
Section: Cytokines and Growth Factors In Cartilage Regenerationmentioning
confidence: 99%
“…FGF-18, which is highly expressed in the superficial zone of AC, stimulates the expression and accumulation of COL2 and proteoglycan in articular chondrocytes [ 148 , 149 ], preserving cartilage phenotype and thickness to protect AC against degeneration [ 112 ]. DePhillipo et al [ 150 ] confirmed significant improvement in cartilage healing at 6 months after microfracture or osteochondral defect repair in preclinical randomized controlled trials with the use of FGF-18.…”
Section: Cytokines and Growth Factors In Cartilage Regenerationmentioning
confidence: 99%